Expression of adenosine kinase in human mesial temporal lobe epilepsy with hippocampal sclerosis: A preliminary study - Leal, B. (2014)
Background: Adenosine is a ubiquitous homeostatic molecule that acts as an “endogenous neuromodulator”. Adenosine attenuates neuronal activity either presynaptically by inhibiting neurotransmitter release or by controlling neurotransmitter responsiveness at post-synaptic sites. Unbalanced adenosine metabolism has been implicated in pathological conditions such as epilepsy. Adenosine kinase (ADK), synthetized by astrocytes, is the key regulator of extracellular adenosine levels in the brain. Evidences from experimental studies support a role for ADK in brain injury associated with astrogliosis, a morphological hallmark of Mesial Temporal Lobe Epilepsy with Hippocampal Sclerosis (MTLE-HS). In fact, expression of astrocytic ADK was found to be increased in the hippocampus and temporal cortex of MTLE-HS patients. Overexpression of ADK decreases extracellular adenosine and consequently may cause seizures. The aim of this study was to characterize ADK gene expression in MTLE-HS patients. Methods: Previous studies used immunohistochemistry and Western blot analysis to investigate ADK expression. Here we quantified the expression levels of ADK by Real-Time PCR in the hippocampus (lesional and peri-lesional cortical area) of 10 MTLE-HS patients submitted to surgery as compared with 9 autopsy controls with no history of neurological disorders. Results: Our results showed that ADK expression levels were similar in the hippocampus and temporal cortex of MTLE-HS patients when compared to healthy controls. Conclusion: Our preliminary data demonstrate that ADK expression levels are not altered in MTLE-HS. These results do not preclude post-transcriptional ADK abnormalities at both protein and functional levels. Our results should be confirmed in a larger cohort as well as with complementary methodologies.